Prevalence of mortality caused by injuries at Livingstone University Hospital, Zambia. A retrospective cross-sectional study - Lukundo Siame; Malan Malumani; Chiyeñu O. R. Kaseya; Sergiy Ivashchenko; Leah Nombwende; Sepiso K. Masenga; Benson M. Hamooya; Michelo Haluuma Miyoba (PLoS ONE, 2025)
Background Trauma is a major global public health issue, with an annual death toll of approximately 5 million, disproportionately affecting low- and middle-income countries. Zambia bears a significant burden of trauma-related mortalities, contributing to 7% of all annual deaths and 1 in 5 premature deaths in the country. Despite the significant burden of trauma in our country, few studies have been conducted, with most focusing on high-population centers, and there is a lack of epidemiological data on trauma-related deaths in our region. Therefore, our aim was to estimate the proportion of deaths caused by injuries at Livingstone University Teaching Hospital, a tertiary hospital located in Zambia’s southern province. Methods We conducted a retrospective cross-sectional study from June 22, 2020, to June 22, 2021, among 956 individuals from 1 month old (29 days of age) to 100 years. Demographic and clinical data were collected from patient’s records from Accident and Emergency department. Data analysis included descriptive statistics, chi square, mann-whitney test and multivariable logistic using forward stepwise generalized linear model equations (GLM) to identified factors associated with mortality, with a significance level set at p < 0.05. Data were analyzed using STATA version 15. Results Among the study participants, the median age was 26 years (interquartile range (IQR) 15, 37) and the majority were males (74.2%, n = 709). Prevalence of mortality was 1.0% (n = 10). The deaths were caused by burns (60%, n = 6), violence (30%, n = 3), and traffic accidents (10%, n = 1). Among those who died, the majority of the trauma occurred at home (90%, n = 9), followed by road (10%, n = 1) and were as a result of burns (60%, n = 6) and community violence (30%, n = 3). Survivors had significantly higher treatment costs (ZMK 9,837 vs. ZMK 6,037, p<0.005). Having burns (AOR: 1.06, 95% CI: 1.05, 1.09, p< 0.001) and hospital stay of one day (AOR: 1.04, 95% CI: 1.02, 1.05, p< 0.001) was positively associated with mortality, while hospital stay of more than five days (AOR: 0.98, 95% CI: 0.96, 0.99, p = 0.002) was negatively associated with mortality. Conclusion The prevalence of death due to trauma was relatively low, with the majority experiencing multiple traumas. Burns were the most common cause and were associated with death, occurring within a day of hospitalization. The findings underscore the need for targeted preventive measures, improved access to quality emergency trauma care, and rehabilitation services, especially among patients with burns.